Factors Associated with Stunting among 24–35-Month-Old Kalinga Indigenous Children in Pinukpuk, Kalinga, Philippines: A Case-Control Study - Piniliw, Marites B; Africa, Leila S.; Agne, Jaidee P. (Jurnal Gizi dan Pangan, 2021)
The study identified the risk factors associated with stunting among 24.35 months indigenous children in Pinukpuk, Kalinga using case control design; 174 children (87 cases and 87 controls) were randomly selected and information were collected through interview and anthropometric measurements. Odds ratio and 95% confidence interval were used to measure association. Low birth weight, child drinking brewed or commercial coffee, no nutrient supplement intake since birth, and incomplete immunization were child risk factors of stunting. Exclusive breastfeeding from 0.6 months and weaning at >12 months have protective effect. Antenatal visits <4 times, fatherfs height <5 feet, parentfs education below secondary level were parental risk factors. Nuclear household and size of less than five members have protective effect against stunting. Having food restrictions among lactating mothers was cultural risk factors. Mothersf insufficient knowledge on exclusive breastfeeding, frequency of and proper way of breastfeeding, continuance of breastfeeding beyond 6 months, benefit of exclusive breastfeeding for six months to mothers and low self-confidence in preparing complementary food were all associated with stunting. Motherfs positive attitude on benefits of frequent feeding was found to have protective effect against stunting. Thus, these family factors could be used when designing an action plan to address the problem of stunting among the indigenous Kalinga children.